Design, Synthesis, In Silico Studies and Inhibitory Activity towards Bcr-Abl, BTK and FLT3-ITD of New 2,6,9-Trisubstituted Purine Derivatives as Potential Agents for the Treatment of Leukaemia - Bertrand, Jeanluc; Dostálová, Hana; Kryštof, Vladimír; Jorda, Radek; Delgado, Thalía; Castro-Alvarez, Alejandro; Mella, Jaime; Cabezas, David; Faúndez, Mario; Espinosa-Bustos, Christian; Salas, Cristian O (Pharmaceutics, 2022)
We report 31 new compounds designed, synthesized and evaluated on Bcr-Abl, BTK and FLT3-ITD as part of our program to develop 2,6,9-trisubstituted purine derivatives as inhibitors of oncogenic kinases. The design was inspired by the chemical structures of well-known kinase inhibitors and our previously developed purine derivatives. The synthesis of these purines was simple and used a microwave reactor for the final step. Kinase assays showed three inhibitors with high selectivity for each protein that were identified: 4f (IC50 = 70 nM for Bcr-Abl), 5j (IC50 = 0.41 μM for BTK) and 5b (IC50 = 0.38 μM for FLT-ITD). The 3D-QSAR analysis and molecular docking studies suggested that two fragments are potent and selective inhibitors of these three kinases: a substitution at the 6-phenylamino ring and the length and volume of the alkyl group at N-9. The N-7 and the N-methyl-piperazine moiety linked to the aminophenyl ring at C-2 are also requirements for obtaining the activity. Furthermore, most of these purine derivatives were shown to have a significant inhibitory effect in vitro on the proliferation of leukaemia and lymphoma cells (HL60, MV4-11, CEM, K562 and Ramos) at low concentrations. Finally, we show that the selected purines (4i, 5b and 5j) inhibit the downstream signalling of the respective kinases in cell models. Thus, this study provides new evidence regarding how certain chemical modifications of purine ring substituents provide novel inhibitors of target kinases as potential anti-leukaemia drugs.